Design and Application of High School Scratch Programming Instructional Activities for Computational Thinking Development - Yang, Hairu; Li, Yuhang; Liang, Zhou; Chen, Hongyan; Chen, Meifen; Zhang, Xiaoyu (2025 7th International Conference on Computer Science and Technologies in Education (CSTE), 2025)
With the increasing importance of computational thinking in the digital age, Scratch programming programs have performed well in developing students' computational thinking skills. Nevertheless, the authors found that current high school students still commonly suffer from poor computational thinking skills and low academic satisfaction. Therefore, this study designed a model of high school scrath programming teaching activities for developing computational thinking, using constructivist learning theory, achievement motivation theory, and Dewey's behavioral view of learning as theoretical guides, selected two classes of sophomore students in a high school in China as the research subjects, and conducted a quasi-experimental study to validate the model. The results of the study show that the teaching mode can effectively improve students' abilities in abstraction, decomposition, algorithms, evaluation and generalization, and it is further found that the effect of improving abstract thinking and generalization thinking is most prominent.